Analisis Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Siswa dalam Materi Bilangan Bulat Ditinjau dari Motivasi Belajar - Nuraini, Nuraini; Sandie, Sandie; Irvandi, Wandra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze differentiated lessons on student learning outcomes in whole number material in terms of learning motivation. The research method used in this research is qualitative with a descriptive research form. The subjects of this research were 6 class VII students at SMPN 01 Sungai Kakap, namely using differentiated learning in content, process, and product. The instruments used in this research are non-test instruments, namely learning motivation questionnaires, observation security sheets, documentation, and interview guides. Based on the results of research that has been conducted, it can be concluded that student learning motivation influences learning outcomes in differentiated learning.